Impact of Inventory Management on Profitability of the Manufacturing Company: Empirical Evidence from Himalayan Distillery Limited - Vaidya, Rashesh (INTELLIGENCE Journal of Multidisciplinary Research, 2023)
Better inventory management is essential for preventing excess costs and waste of money for the distillery. The funds used in managing inventory could be used in branding and marketing the products. Hence, the paper tries to find an impact of inventory management on the profitability of one of the listed companies of Nepal, Himalayan Distillery Limited. A paper followed a correlation research design using secondary data for the sampled company. The paper found a high degree of positive correlation between closing stocks and raw materials and also closing stocks with packaging and other materials. A regression analysis reflected no significant relationship or statistical association between the inventory-related variables and the profitability of the sample company.